THE INDUCTION OF SPRING WHEAT RESISTANCE TO ROOT ROTS AGENTS UNDER THE INFLUENSE OF FUNGUS CHAETOMIUM COCHLIODES PALLISER - Є. П. Копилов; С. П. Надкерничний; Л. О. Білявська; О. В. Голубець (Mìkrobìologìâ ì Bìotehnologìâ, 2010)
The effectiveness of saprophyte fungus Chaetomium cochliodes 3250 usage as an inductor of spring wheat plants resistance to root rots agents was achieved. The content of fatty acids in cultural medium was investigated. It was found out that C. cochliodes 3250 produced arachidonic acid accumulating it in cultural medium. Arachidonic acid is a biogenic elicitor which induces an immune answer in plats tissues in response to pathogenes action and unfavourable environment. The ability of C. cochliodes 3250 to produce arachidonic acid is one of the factors of rising up spring wheat plants resistance to root rot agents during its usage.